Edukasi Keluarga Berencana Pada Wanita Usia Subur (PUS) Di Kecamatan Malakaji Kabupaten Gowa - Pratiwi Bayuningrum; Satiani Dalle; Safira Welay (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
One of the significant issues faced by developing countries, including Indonesia, is the problem of rapid population growth. To overcome this problem, the Indonesian government has implemented the Family Planning (KB) Program. The family planning program provides an opportunity for residents to regulate the distance between child births or reduce the number of births by using various contraceptive methods, both hormonal and non-hormonal. The aim of this Community Service Activity is to improve maternal and child health services, with the hope of controlling the rate of population growth. This activity was carried out by providing information about family planning and free family planning services to 20 WUS who were family planning acceptors in Malakaji District, Gowa Regency. After free family planning services, there was a question and answer session about family planning and evaluation monitoring was carried out. The results of this activity showed that the family planning participants were able to answer questions well and some of them were willing to use IUD or implant family planning. From the results of this activity, it can be seen that knowledge about family planning increased after the outreach was carried out. Before the counseling was carried out, the majority of knowledge was lacking, 12 mothers or 80%. Meanwhile, the mother's knowledge before being given counseling was lowest at Good knowledge, namely 1 person or 6.67%. Mothers' knowledge after counseling was highest in good knowledge, namely 14 people or 93.33%, so it can be concluded that Community Service activities, in the form of counseling about family planning, had a positive impact on WUS in the area and succeeded in increasing family planning knowledge